2021
DOI: 10.3390/md19070358
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Components as Potential Modulators of the Gut Microbiota

Abstract: Macroalgae, or seaweeds, are a rich source of components which may exert beneficial effects on the mammalian gut microbiota through the enhancement of bacterial diversity and abundance. An imbalance of gut bacteria has been linked to the development of disorders such as inflammatory bowel disease, immunodeficiency, hypertension, type-2-diabetes, obesity, and cancer. This review outlines current knowledge from in vitro and in vivo studies concerning the potential therapeutic application of seaweed-derived polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 383 publications
(431 reference statements)
0
37
0
Order By: Relevance
“…A number of studies have shown that carrageenan induces colitis and is related to the gut microbiota of the host [68,73]. Porphyran and ulvans also have some anti-metabolic syndrome function, but there are few studies on related mechanism and its effect on gut microbiota [69,74].…”
Section: Regulation Of Msps On Gut Microbiotamentioning
confidence: 99%
“…A number of studies have shown that carrageenan induces colitis and is related to the gut microbiota of the host [68,73]. Porphyran and ulvans also have some anti-metabolic syndrome function, but there are few studies on related mechanism and its effect on gut microbiota [69,74].…”
Section: Regulation Of Msps On Gut Microbiotamentioning
confidence: 99%
“…Seaweeds are a rich source of components that may exert advantageous effects on the mammalian gut microbiota through the improvement of bacterial abundance and diversity. A recent comprehensive review of in vitro and in vivo studies by Shannon and colleagues [ 50 ] considered the potential therapeutic potential of seaweed-derived polysaccharides, peptides and polyphenols to modulate the gut microbiota through diet. They reported that, in several studies, these components could act as prebiotics and positively modulate the gut microbiota [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent comprehensive review of in vitro and in vivo studies by Shannon and colleagues [ 50 ] considered the potential therapeutic potential of seaweed-derived polysaccharides, peptides and polyphenols to modulate the gut microbiota through diet. They reported that, in several studies, these components could act as prebiotics and positively modulate the gut microbiota [ 50 ]. In the current work, we observed modest changes in the levels of quantified bacteria in stool samples (FISH analysis) following agar and alginate treatments, including a significant increase in Faecalibacterium prausnitzii in subjects consuming agar LMWP.…”
Section: Discussionmentioning
confidence: 99%
“…with interesting therapeutic properties. These polysaccharides have uses as gelling agent, nutritional supplement, with antioxidants [109][110][111][112], and are antiallergic [32,113], show tyrosinase inhibitory activity [62], protection against ultraviolet B radiation [59], anti-inflammatory and antitumoral activity, and can promote the growth of beneficial bacteria in intestinal microbiota [76,113] without toxicity in mice models [114,115]. Agarooligosaccharides (AOS) and carrageenan-oligosaccharides (COS) present enhanced biological properties compared to native ones, in relation to prebiotic, antitumoral, and antioxidant actions, related to their chemical structure, molecular weight, degree of polymerization, and the flexibility of the glycosidic linkages [116].…”
Section: Component Properties/activities Seaweed Referencesmentioning
confidence: 99%